A influência do comportamento sedentário no risco cardiovascular de policiais militares de Pinheiro/MA - SILVA, Francisco Eduardo Lopes da (2024)
Objective: To investigate the correlation between sedentary behavior and cardiovascular risk in military police officers from Pinheiro/MA. Methods: This was a cross-sectional study in which volunteers were assessed using questionnaires (sociodemographic, readiness for physical activity, International Physical Activity Questionnaire - short version, and sedentary behavior). Anthropometric, hemodynamic, body composition, and physical fitness measurements were conducted. Simple linear regression was used to analyze factors correlated with cardiovascular risk, and multiple regression was applied to determine the contribution power of each variable. For the comparison between cardiovascular risk (CVR) groups (Low CVR vs. Moderate CVR), independent sample t-tests were used. Normally distributed data were presented as means and standard deviations, while frequencies and percentages were used for categorical variables. Data analysis was performed using SPSS software, and graphs were created with GraphPad Prism, version 9.0. Results: A total of 53 volunteers (46 males and 7 females) completed all stages of the study. Among all findings, it is noteworthy that time spent sitting while using a cellphone (p=0.015) and time spent sitting during transportation (p=0.012) were correlated with cardiovascular risk. Additionally, cellphone use (β=0.309), elevated systolic blood pressure (β=0.399), and reduced serum levels of high-density lipoprotein (β=-0.301) were identified as predictors of cardiovascular risk. Conclusion: Time spent in sedentary behavior related to cellphone use, as well as time spent sitting during transportation, are correlated with cardiovascular risk. Moreover, systolic blood pressure (SBP) (mmHg) demonstrated the highest weight in the model (β=0.399) and individual contribution (23%) to CVR, followed by HDL levels, weight (β=0.301) with a contribution of 16%, and time spent sitting using a cellphone (β=0.309) with a contribution of 11%.